Sustainability practices at higher education institutions in Asia - Filho, Walter Leal; Dinis, Maria Alzira Pimenta; Sivapalan, Subarna; Begum, Halima; Ng, Theam Foo; Al-Amin, Abul Quasem; Alam, Gazi Mahabubul; Sharifi, Ayyoob; Salvia, Amanda Lange; Kalsoom, Qudsia; Saroar, Mustafa; Neiva, Samara (Emerald Publishing Limited, 2021)
Purpose: It is still unclear how Asian universities incorporate the theory or practice of sustainable development (SD) in their research and education programmes. To address this gap, the purpose of this paper is to report on a study that has examined how universities in Asian countries handle and address matters related to SD. Design/methodology/approach: The study used a bibliometric analysis and an online survey-method. The online survey data were analysed through descriptive analysis and one-sample student’s t-test. Findings: The study indicates that there is considerable variation among the Asian countries regarding sustainability practices in higher education institutions (HEIs). The HEIs in far eastern countries, such as Indonesia, Malaysia and Thailand are perceived to demonstrate more sustainability practices. Research limitations/implications: Even though a substantial number of participants participated in the survey, it did not cover all Asian countries. The online survey was carried out over a limited period of time, and not all HEIs in the field may have received information about the study. Practical implications: Asia is the largest continent facing a number of sustainability challenges. In this context, the contribution of HEIs is very important. The findings of the current study may serve as a baseline for Asian HEIs to take more initiatives towards SD goals, as HEIs are responsible for the education and training of hundreds of thousands of students who will be occupying key positions in industry, government or education in the coming years. Originality/value: The study contributes to the existing literature in two distinct ways. First, it was possible to develop a comprehensive instrument to measure sustainability practices in HEIs. Second, this study has filled the gap of the scarcity of studies regarding sustainability practices in HEIs in Asia.